Host Attraction and Selection in the Swede Midge (Contarinia nasturtii) - Boddum, Tina; Molnár, Béla P.; Hill, Sharon R.; Birgersson, Göran Å. O.; Hansson, Bill S.; Abreha, Kibrom B.; Andreasson, Erik; Hillbur, Ylva (Frontiers in Ecology and Evolution, 2018)
Gall midges (Diptera: Cecidomyiidae) are a speciose family that, as adults, are short lived (lasting only a few days), they use olfactory cues for host and mate localization, and their host plant specificity is a key characteristic of the family. These traits make them good models with which to study the role of olfaction in speciation. The overall objective of this study was to analyze the host selection behavior of the gall midge, Contarinia nasturtii, a crucifer specialist that also is a crucifer pest. Here, we demonstrate that the host specificity of gravid C. nasturtii females was initiated by the olfactory-driven host plant choice during oviposition. Olfactory preference of the female, while narrow, encompassed more plants than were accepted for egg-laying, indicating that other factors following the initial olfactory attraction are involved in ultimate host choice. Similarly, C. nasturtii showed flexibility in host plant choice depending on which plants were available for oviposition. Larvae developed on host plants selected by females for oviposition. This slightly broader range of olfactory preference over acceptance, and the flexibility in host choice, might be the basis for the rapid speciation reported in the gall midge family. Furthermore, we assessed whether ubiquitous and/or family-specific plant odors are involved in the attraction of gravid C. nasturtii to their hosts. For that, we used the crucifer Arabidopsis thaliana, which has a broad range of defined ecotypes and large number of mutants. The attraction of C. nasturtii to two A. thaliana-types were tested; one that does not produce the ubiquitous green leaf volatiles (Columbia, Col-0), and a knock-out mutant which does not produce the crucifer-specific glucosinolates. Surprisingly, C. nasturtii was attracted to both types, indicating that neither of these compounds, nor their breakdown products (e.g. isothiocyanates), are essential for C. nasturtii host attraction.